Three novel Cu(II), Cd(II) and Cr(III) complexes of 6-Methylpyridine-2-carboxylic acid with thiocyanate: Synthesis, crystal structures, DFT calculations, molecular docking and alpha-Glucosidase inhibition studies - Avci, Davut; Alturk, Sumeyye; Sonmez, Fatih; Tamer, Omer; Basoglu, Adil; Atalay, Yusuf; Kurt, BELMA; ZENGİN KURT, BELMA; Dege, Necmi (My University, 2018)
Novel complexes of 6-methylpyridine-2-carboxylic acid and thiocyanate ([Cu(NCS)(6-mpa)(2)], (1); [Cd(NCS)(6-mpa)](n), (2); [Cr(NCS)(6-mpa)(2)center dot H2O], (3)} were synthesized, and their structures were characterized by XRD analysis, FT-IR and UV-Vis spectroscopic techniques. The inhibitory activities of the synthesized complexes (1-3) on alpha-glucosidase were determined by using genistein reference compound. Furthermore, the optimized geometry and vibrational harmonic frequencies for the complexes 1-3 were obtained by DFT/HSEh1PBE/6-311G(d,p)/LanL2DZ level. Electronic spectral properties were examined by using TD-DFT/FISEh1PBE/6-311G(d,p)/LanL2DZ level with CPCM model. Additionally, major contributions to the electronic transitions were determined via Swizard program. The refractive index, linear optical and non-nonlinear optical parameters of the complexes 1-3 were investigated at HSEh1PBE/6 -311G(d,p) level. The docking studies of the complexes 1-3 to the binding site of the target protein (the template structure S. cerevisiae isomaltase are fulfilled. Lastly, natural bond orbital analysis was used to investigate inter- and intra-molecular bonding and interaction among bonds. (C) 2018 Elsevier Ltd. All rights reserved.